Genes that control neuromuscular specificity in Drosophila. - van Vactor, D.; Sink, H.; Fambrough, D.M.; Tsoo, R.; Goodman, C.S. (Cell, 1993)
In each abdominal hemisegment of the Drosophila embryo, an array of 30 muscle fibers is innervated by about 34 motoneurons in a highly stereotyped and cell-specific fashion. To begin to elucidate the molecular basis of neural specificity in this system, we conducted a genetic screen for mutations affecting neuromuscular connectivity. We focus on 5 genes required for specific aspects of pathway (beaten path, stranded, and short stop) and target (walkabout and clueless) recognition. The different classes of mutant phenotypes suggest that neural specificity is controlled by a hierarchy of molecular mechanisms: motoneurons are guided toward the correct region of mesoderm, in many cases navigating a series of choice points along the way; they then display an affinity for a particular domain of neighboring muscles; and finally, they recognize their specific muscle target from within this domain.